The immunodominant major histocompatibility complex class I-restricted antigen of a murine colon tumor derives from an endogenous retroviral gene product. - Huang, A Y (1996)
Tumors express peptide antigens capable of being recognized by tumor-specific cytotoxic T lymphocytes (CTL). Immunization of mice with a carcinogen-induced colorectal tumor, CT26, engineered to secrete granulocyte/macrophage colony-stimulating factor, routinely generated both short-term and long-term CTL lines that not only lysed the parental tumor in vitro, but also cured mice of established tumor following adoptive transfer in vivo. When either short-term or long-term CTL lines were used to screen peptides isolated from CT26, one reverse-phase high performance liquid chromatography peptide fraction consistently sensitized a surrogate target for specific lysis. The bioactivity remained localized within one fraction following multiple purification procedures, indicating that virtually all of the CT26-specific CTL recognized a single peptide. This result contrasts with other tumor systems, where multiple bioactive peptide fractions have been detected. The bioactive peptide was identified as a nonmutated nonamer derived from the envelope protein (gp70) of an endogenous ecotropic murine leukemia provirus. Adoptive transfer with CTL lines specific for this antigen demonstrated that this epitope represents a potent tumor rejection antigen. The selective expression of this antigen in multiple non-viral-induced tumors provides evidence for a unique class of shared immunodominant tumor associated antigens as targets for antitumor immunity.